Assessing compliance to reporting mandates in glioblastoma-related clinical trials - Nicholas Kendall; Julian S. Rechberger; Abdelrahman M. Hamouda; Mark Cwajna; Sherief Ghozy; Kogulavadanan Arumaithurai; David F. Kallmes (PLoS ONE, 2025)
Introduction Accurate and timely reporting of scientific knowledge is crucial to clinical research ethics. ClinicalTrials.gov allows researchers to register trials and report results to the public and scientific community. Despite FDA reporting mandates, compliance with the required 12-month window remains low. Given glioblastoma’s (GBM) aggressive nature, timely reporting is especially important for advancing research and benefiting patients. This study aimed to assess GBM trial reporting rates on ClinicalTrials.gov and identify factors related to non-compliance. Methods We utilized a previously published algorithm to identify studies on ClinicalTrials.gov likely mandated to report. We obtained the titles, status, results, phases, funding type, intervention type, study design and type, location, and all available trial dates. Kaplan-Meier analysis evaluated reporting times, and Cox regression models identified factors associated with reporting within five years. Results We identified 255 GBM-related trials likely mandated to report. 13% reported results within the 12-month deadline, while 82.7% reported within five years. Factors significantly associated with lower reporting rates at five years were biological interventions (HR 0.61, 95% CI: 0.37–1.00, p = 0.049), Phase 1–2 trials (HR 0.65, 95% CI: 0.46–0.91, p = 0.014), and studies with quadruple masking (HR 0.19, 95% CI: 0.04–0.93, p = 0.040). Conclusion For GBM-related trials, noncompliance with reporting mandates remains a major issue. Reporting within 12 months was only 13%. No factors influenced reporting by 12 months, but multiple factors influenced five-year reporting. Further research is needed to understand these associations and create targeted incentives to increase transparency through timely reporting of GBM-related trials.